The Personality Structure and Defense Mechanism of The Main Character In The Euphoria Series (2019) - Safitri Rulita (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2023)
Abstract The research presented here focuses on Rue Bennett, the protagonist of the film series Euphoria. Using Sigmund Freud's psychoanalytic theory as a guide, the goal of this study is to determine Rue Bennett's personality structure and analyze her protective mechanisms. In this study, qualitative approaches and descriptive analysis are utilized to analyze data through the lens of psychoanalytic theory in relation to personality structure and defensive mechanisms in films. Utilizing these methodologies, this hypothesis is incorporated into the research. The information is gathered from both the script's speech and the film's pictures. Rue Bennett, a 17-year-old adolescent, has developed a drug dependence in order to reduce the overwhelming anxiety she encounters, according to the findings. As a result, Rue's anxiety problem has caused an uneven personality structure as a consequence of the ailment. Her id takes precedence over her superego when it comes to the causes of her anxiety and panic attacks. Even though Rue employs a variety of defensive mechanisms, including denial, projection, and fantasy. These are insufficient to assist her in overcoming her traumatic experiences and anxieties.